Pemanfaatan Zeolit Alam Malang Sebagai Adsorben Pada Pemurnian Crude Glycerol Dalam Kolom Adsorpsi - Oktaviani Tri Utami; Mustain Zamhari; Robert Junaidi (Universitas Batanghari Jambi, 2026)
Glycerol is a byproduct of the biodiesel transesterification reaction that has a low purity level, also known as crude glycerol. Approximately 10-20% by weight of glycerol is produced as a byproduct of each biodiesel transesterification reaction. Crude glycerol contains many impurities, which has led to its suboptimal management. To reduce waste generated from the biodiesel transesterification reaction, further purification is necessary to produce high-purity glycerol with significant market value that can be used in various industries. Therefore, researchers aim to utilize natural zeolite from Malang as an adsorbent in the purification of crude glycerol. This study is conducted to understand the impact of chemical and physical activation on Malang natural zeolite in enhancing its characteristics as an adsorbent and to determine the optimal conditions (residence time and adsorbent weight) for achieving the highest purity glycerol through the adsorption process. The natural zeolite from Malang was prepared by activation with H2SO4 and calcined with 3 hours at 500°C. This was followed by an adsorption method using an adsorption column with varying residence times (30, 45, 60, 75, and 90 minutes) and adsorbent weights (20g, 40g, and 60g). The chemical and physical activation of Malang natural zeolite successfully enhanced its adsorption capacity by increasing the active pore size (0.97 μm – 4.42 μm) and reducing impurity ions, as well as raising the Si/Al ratio to 4.503. The optimal glycerol purity achieved was 86.33% with adsorbent weight of 60 grams and a residence time of 60 minutes.